Diabetic painful truncal neuropathy with hypohidrosis and facial palsy. Issue 3 (24th February 2020) - Tsunoda, Keiichiro; Omote, Yoshio; Hishikawa, Nozomi; Ikegami, Ken; Nakano, Yumiko; Sato, Kota; Takemoto, Mami; Ohta, Yasuyuki; Yamashita, Toru; Deguchi, Kentaro; Abe, Koji
Abstract: Truncal neuropathy is a rare phenotype of diabetic neuropathy. Here, we report the first case of diabetic painful truncal neuropathy complaining of back pain with hypohidrosis confirmed by a sweat test accompanied by cranial nerve palsy. The patient had poorly controlled type 2 diabetes mellitus and suffered from back pain followed by facial palsy. After pulse therapy with methylprednisolone facial palsy improved, but back pain was intractable with a loss of body weight. The sweat test showed hypohidrosis on the back and soles on his feet. Sural nerve biopsy revealed decreased small fibers and mild axonopathy. After palliative therapy, his symptoms gradually improved.